PENGARUH PENAMBAHAN FUEL OIL ADDITIVE (FOA) TERHADAP PERFORMA DAN KONSUMSI BAHAN BAKAR MESIN DIESEL BERBAHAN BAKAR B20 - Moch. Syaiful Anwar; Mochamad Shaleh (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2023)
This study aimed to analyze the effect of Fuel Oil Additive (FOA) on the performance and fuel consumption of diesel engines fueled with B20 biodiesel. The research used an experimental quantitative method by comparing the Specific Fuel Consumption (SFC) values of diesel engines operating with B20 fuel and B20 mixed with FOA under different loading conditions. The tests were conducted on a 6DV-32 diesel engine generator with loading variations of 50%, 75%, and 100%. The results showed that the addition of FOA improved fuel efficiency at medium and high engine loads. At 75% load, the SFC value decreased from 0.309 liter/kWh to 0.291 liter/kWh, representing a reduction of 5.82%. At 100% load, the SFC value decreased significantly from 0.292 liter/kWh to 0.246 liter/kWh, with an efficiency improvement of 15.75%. However, at 50% load, the SFC value increased from 0.312 liter/kWh to 0.329 liter/kWh or by 5.45%, indicating that FOA performance was less effective at low engine loads. The findings indicate that the use of Fuel Oil Additive enhances combustion quality and improves fuel consumption efficiency, particularly under high loading conditions. Therefore, B20+FOA has the potential to be applied as an alternative fuel solution for improving diesel engine operational efficiency.